A norfloxacin-nicotinic acid cocrystal: Mechanochemical synthesis, thermal and structural characterization and solubility assays - Ferreira, Patricia Osorio [UNESP]; de Almeida, Amanda Cosmo [UNESP]; dos Santos, Éverton Carvalho [UNESP]; Droppa, Roosevelt; Ferreira, Fabio Furlan; Kogawa, Ana Carolina; Caires, Flávio Junior [UNESP] (Elsevier, 2020)
This work reports the mechanochemical synthesis and characterization of a cocrystal formed by norfloxacin (NOR) and nicotinic acid (NCA). The thermal analysis provided the thermal stability and appropriated stoichiometry of NOR-NCA cocrystal. In addition, the crystalline structure and the coordination sites were obtained through Fourier-transform infrared spectroscopy (FTIR) and X-ray powder diffraction (XRPD). This allowed the determination of NOR-NCA interaction in the cocrystal state: the amine group of NOR interacts simultaneously with the aromatic nitrogen and the hydroxyl of the carboxyl group of NCA. Moreover, NOR-NCA crystallized in the monoclinic crystal system, space group Pa, and Z = 4, Z’ = 2. Finally, solubility assays showed an increase of NOR solubility of 2 times in pH 6.1 buffer solution. On the other hand, the cocrystal did not show a significant change in NOR solubility in pH 3.0 buffer solution, while presented a slight decrease in pH 8.5 buffer solution, which shows a pH-dependency.
Keywords: Cocrystal; Crystal structure; Norfloxacin; Solubility; Thermal analysis; X-ray powder diffractometry